EUROPÉANISATION INSTITUTIONNELLE DES RELATIONS ENTRE L’ÉTAT ALBANAIS ET DES INSTITUTIONS RELIGIEUSES AU COURS DES ANNÉES 1920-1930 - Ljarja, Nertila Haxhia (European Scientific Journal, ESJ, 2014)
The purpose of this paper is to focus on the 1920s and 30s, precisely during a very important period of slow development but continuous trial of de-Ottomanization of the institutional structures of the Albanian government. Quite a difficult process due to a variety of reasons, all related to the inheritance left by the Ottoman empire in the country. The subject of this study will focus particularly on the commitment of the Albanian Catholic clergy in the system of relations between the Albanian government, specifically the Republic (1925-1928) and the Monarchy Zogu (1928-1939) and the Roman Catholic Church in Albania. Within this relationship analysis, which has already been studied, what makes this study particular is the optics analysis of some unpublished documents that were unknown to previous researchers of this matter.